Dietary restraint and subjective well-being in university students in Chile - Berta Schnettler; Horacio Miranda; José Sepúlveda; Ligia Orellana; Soledad Etchebarne; Germán Lobos; Marcos Mora; Marianela Denegri; Klaus G. Grunert (Nutrición Hospitalaria, 2014)
Objective: To characterize university students typologies according to chronic food restriction, satisfaction with life and food consumption. Materials and method: A questionnaire was applied on a non-probability sample of 369 male and female students from five Chilean universities. The questionnaire included: Revised Restraint Scale (RRS), Satisfaction with Life Scale (SWLS), Satisfaction with Food-related Life (SWFL) and the Health-related Quality of Life Index. The survey included food and drink consumption habits, weight and approximate height and sociodemographic variables. Results: Two factors in the RRS were detected by exploratory factor analysis: Preoccupation with Diet (PD) and Weight fluctuations (WF). A confirmatory factor analysis validated the bifactor structure of the RRS with an acceptable adjustment kindness. The cluster analysis allowed a distinction of four typologies with a significant variation in PD, WF, SWLS and SWFL scoring, number of days with mental health problems, frequency of alcoholic drinks consumption, restraint on the consumption of certain foods, drinks and spices, consumption frequency of fruit out of the main meals and types. Typologies did not differ on their body mass index. Conclusions: Both, students preoccupied with diet and those who are not, experience higher levels of satisfaction with life and with food. Lower levels of global life satisfaction and satisfaction with food are related with the fluctuations in weight.